1988
DOI: 10.1007/bf02544521
|View full text |Cite
|
Sign up to set email alerts
|

NMR relaxation studies to explore the role of emulsifier in tristearin polymorphic transformation

Abstract: Proton magnetic resonance measurements were performed onα andβ polymorphs of tristearin crystals. T1 relaxation time was measured with the Bruker PC Minispec at 20 MHz and 37° on the pure triglyceride crystals and therefore on tristearin crystallized in the presence of different solid surfactants. A significant negative correlation for T1 values and different compositions ofα andβ polymorphs in a mechanical mixture was found. The shortening of T1 relaxation time of theβ form was found to be different for the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…(Table 4). This T 1 value, corresponding to the solid phase of fat, is slightly smaller than the one obtained with pure triolein (240 ms); this difference could be due to a difference in the crystallization state of the fat in the presence of the emulsifier (31). It would induce a less compact state of solid fat.…”
Section: Oil-in-watermentioning
confidence: 50%
“…(Table 4). This T 1 value, corresponding to the solid phase of fat, is slightly smaller than the one obtained with pure triolein (240 ms); this difference could be due to a difference in the crystallization state of the fat in the presence of the emulsifier (31). It would induce a less compact state of solid fat.…”
Section: Oil-in-watermentioning
confidence: 50%
“…The current results are in agreement with previous studies performed with one or two TAs at a single temperature. [6,7,13,14] The present study demonstrated that a general dynamic behavior can be observed for TAs at low or high NMR field whatever the chain length and the temperature studied. The results obtained from the proton T 1 measurements displayed a minimum ratio of 1 : 10 between the α and the β forms for the TA family chosen.…”
Section: Discussionmentioning
confidence: 76%
“…[6] Others T 1 measurements have suggested that the mobility of the terminal methyl group of tristearin was more constrained in the β polymorph than in the α polymorph. [7] T 1 relaxation time measurements have also made it possible to the study of lipid crystallization in complex food systems. [11] TAs have also been investigated using high-field NMR spectrometry, and this has allowed the spectral assignment of tripalmitin and tristearin in the three polymorphic forms.…”
Section: Introductionmentioning
confidence: 99%
“…Azoury [10] obtained a correlation coefficient of −0.991 between the average T 1 of a mixture of tristearin and the percentage of the a form in a mixture of α and β forms. We wanted to verify that the quantitative aspect of distributions could be applied to mixtures over the whole range of percentages.…”
Section: Repeatabilitymentioning
confidence: 99%
“…In contrast, the T 1 of the α form of tristearin (hexagonal form) has been measured at 250 ms, while that of the β form (triclinic form) is 1.7 s [10]. According to Azouri [10], Norton [11] was the fi rst to use the parameter T 1 to diffe re n t i ate poly m o rp h i c forms.…”
Section: Introductionmentioning
confidence: 99%